CompTIA CySA+ Cybersecurity Analyst Certification Passport (Exam CS0-002) - Rogers, Bobby E. (McGraw-Hill Education, 2021)
Focused coverage of every topic on the current version of the CompTIA CySA+ exam Get on the fast track to becoming CompTIA CySA+ certified with this affordable, portable study tool. Inside, cybersecurity professional Bobby Rogers guides you on your career path, providing expert tips and sound advice along the way. With an intensive focus only on what you need to know to pass CompTIA CySA+ Exam CS0-002, this certification passport is your ticket to success on exam day. Designed for focus on key topics and exam success: List of official exam objectives covered by domain Exam Tip element offers expert pointers for success on the test Key Term highlights specific term or acronym definitions key to passing the exam Caution notes common pitfalls and real-world issues as well as warnings about the exam Tables, bulleted lists, and figures throughout focus on quick reference and review Cross-References point to an essential, related concept covered elsewhere in the book Practice questions and content review after each objective section prepare you for exam mastery Covers all exam topics, including: Threat and vulnerability management Threat data and intelligence Vulnerability management, assessment tools, and mitigation Software and systems security Solutions for infrastructure management Software and hardware assurance best practices Security operations and monitoring Proactive threat hunting Automation concepts and technologies Incident response process, procedure, and analysis Compliance and assessment Data privacy and protection Support of organizational risk mitigation Online content includes: Customizable practice exam test engine for CS0-002 200+ realistic multiple-choice and performance-based practice questions and in-depth explanations.